Composition of pelagic fish in commercial landings of the longline fishery in the Costa Rica Pacific during 2015-2021 - Allison Centeno-Chaves; Allison Centeno-Chaves; Marina Marrari; Fausto Arias-Zumbado; Andrea García-Rojas; Moisés Mug-Villanueva (Frontiers in Marine Science, 2025)
Longline fishing in the Pacific of Costa Rica targets multiple species of large pelagic fishes and faces challenges in assessment due to lack of data. This study analyzes landing data of pelagic fish in this fishery using unconventional statistical methods, to better understand the dynamics and provide recommendations for improving data collection and analysis. Landing data reported during 2015-2021 were examined. A descriptive and comparative analysis of landings was conducted using Spearman correlation tests and Non-Metric Multidimensional Scaling (NMDS) to visualize patterns in catch composition. Permutational Multivariate Analysis of Variance (PERMANOVA) and Similarity Percentage Analysis (SIMPER) were employed to identify significant differences between fleet types, landing ports, months, and years, as well as species contribution to these differences. The annual mean total landing of large pelagic fish was 7531.01 tons, with 39.14% corresponding to sharks, 24.34% to billfish (Istiophoridae and Xiphiidae), 18.05% to mahi-mahi, and 14.94% to tuna. Statistically significant differences were found between fleet types, landing ports, months, and years. Shark landings were the least correlated (rho=0.36) and had the greatest influence on variation by fleet type. An increase in the similarity of catch composition by port since 2015 was observed. In addition, a shift towards increasingly less selective fishing over the study period was evident. Our findings highlight the urgent need for advanced research methodologies to address gaps in data collection for commercial fisheries in Costa Rica. Improving these methods is crucial to ensure that management policies are based on accurate and comprehensive information. Results highlight the need for a comprehensive strategy involving diverse stakeholders to improve our understanding and ensure the sustainability of fisheries and the preservation of marine ecosystems in Costa Rica.